Strengthening the Capacity Building Government of Rantau Keloyang Village, Bungo Regency, Jambi, Indonesia - Bakar, Abu; Zahlimar; Masnun, Ariyanto; Zulkifli; Mardansyah (HM Publisher, 2023)
The counseling program to strengthen village government capacity building is a systematic effort to increase the knowledge, skills, and attitudes of village government officials and staff. Through this program, they are given training, guidance, and assistance in various aspects of their duties and responsibilities. This community service activity is a comprehensive and real effort from the entire academic community to share knowledge and knowledge related to the effectiveness of capacity building in order to optimize the implementation of a governance-effective government. Community service activities are carried out in the form of workshops and discussions about capacity building in order to optimize the implementation governance effective governance in Rantau Keloyang Village, Bungo Regency, Jambi, Indonesia. This community service activity is quite effective in increasing aspects of the knowledge of village officials regarding aspects of capacity building related to good village governance. Increasing the knowledge score from an average of 47.86 to 88.35 shows the effectiveness of community service activities to strengthen capacity building through workshops and discussions. The counseling program to strengthen village government capacity building is an important step in improving the quality of government and public services at the village level. By increasing the capacity of village governments, it is hoped that they can become agents of development that are effective and competitive and are able to respond better to the demands and needs of the community.